New Russian Literature and Online Journals - Zitzewitz, Josephine von (Wiener Slawistischer Almanach, 2023)
Contemporary Russian literary journals founded after 1991 operate mostlyonline, run their own social media channels and operate as part of larger literaryprojects. While they retain key features of traditional “thick” journals, they have introducedmany new facets into the publishing landscape. This article prioritises journalsthat focus on poetry and examines questions such as the changing significanceof periodicity, the role of social media, the impact of diaspora communities on poetrypublishing and the relationship between the journals of today and samizdat periodicalsof the late Soviet era.